Macrobe sur les vertus des esclaves.: Analyse du chapitre 11 des Saturnales I. - Tóth, Orsolya (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The late antique writer, Macrobius, is of the opinion that virtues can be found in slaves as much as in free men. The author explains his view in his main work, the Saturnalia (I. 11). The aim of this paper is – through the analysis of the passage mentioned above – the examination of precisely what kind of virtues Macrobius attributes to slaves, the context in which these virtues appear, and finally the factors which could have influenced the author while he was writing his text in praise of slaves.